Mobile Based Sharing Class Presentation Display Management - Matias, Junrie B.; Batingal Jr., Narciso M.; Cuasito, Alvin Kleen L.; Tumalaytay, Jenifer T. (International Journal of Interactive Mobile Technologies (iJIM), 2020)
In this paper, we present an application that helps the teachers in identifying slow learners in a class; similarly, the system will help slow learners cope up with their fast learner peers. Specifically, we evaluated the development of the Mobile-based Sharing Presentation Display Management to assist the teachers in identifying students that don’t understand the topic during lectures. Furthermore, the system automatically collects the students’ attendance, allows the learners to interact with each other, learners can ask questions through a messaging facility, while anonymous to their classmates they can inform the teacher to discuss the topic further presented in the current slide or to give them some time to process the item. Developed using open source technologies, the system can run on multiple platforms, including Android and Windows. Few issues arise during the testing; however, findings revealed that both students and teacher perceive the use of the system positively, and they find it very advantageous to improve their performance in the class.